Why Canada Needs REUs - Mulligan, Brendan (Geoscience Canada, 2004)
SUMMARY Problems of earth science involve not only questions of physical science and engineering, but also of the social sciences and humanities. As a fourth-year geo-environmental engineering student, I am increasingly concerned that issues of philosophy and public policy are being neglected in earth science classrooms. Realizing that my scholastic career was narrowing, I sought an opportunity to alleviate this concern and expand my horizon. This summer I participated in just such an opportunity: the Global Climate Change and Society Program, a Research Experience for Undergraduates (REU) sponsored by the National Science Foundation and held in Boulder, Colorado. Throughout the program, students were encouraged to collaborate with peers from around the country, exposed to an outstanding roster of guest speakers, and inspired to reap practical knowledge in disciplines outside their area of specialization. Canadian undergraduates in Earth science would greatly benefit from participating in educational programs of a similar nature. Canada's closest analogue of the National Science Foundation, the Natural Sciences and Engineering Research Council, needs to expand its outreach programs and spearhead a campaign to develop Research Experiences for Undergraduates in Canada.